PENGARUH KUALITAS ANGGARAN DAN PENGETAHUAN TENTANG ANGGARAN TERHADAP PENGAWASAN ANGGARAN - Edisah Putra Nainggolan (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
This study aims to determine how much influence the quality of the budget and the budget of the knowledge of budgetary surveillance in the North Sumatra Police and to determine how much influence the quality of budget and knowledge of budgets together to control the budget at the North Sumatra Police. Based on the type of problem studied, the place and time that is done as well as the techniques and tools used in the study, the method used is the method of causal with descriptive research. Population and sample in this research is to use the technique census numbering 104 people. Research shows that there is a budget to influence the quality of budget control, no influence on the knowledge of the budget and budget control there budgets influence the quality and knowledge of budgets together to control the budget at the North Sumatra Police, according to the coefficient test value t count> t table. Results of regression testing for the variable quality of the budget to the budget control shows the t value> table, then the hypothesis Ha is acceptable. Thus the quality of budgetary positive and significant effect on budget control. While the regression test results for the variable knowledge of budgets to control the budget shows the value of t count> t table, then the hypothesis Ha is acceptable. Thus the quality of budgetary positive and significant effect on budget control. Test results menunujukkan the positive influence together quality budget and knowledge of budgets together to control the budget. This means that with good supervision and good knowledge will provide a good quality budget as well.